Development and physico-chemical analysis of granola formulated with puffed glutinous rice and selected dried Sunnah foods - Agbaje, R; Hassan, CZ; Norlelawati, A; Rahman, AA; Huda-Faujan, N. (Univ Putra Malaysia Press, 2024)
The need for nutritional and functional foods has increased. Consumers, these days, do not eat snacks only to provide satisfaction for their hunger, but also to supply essential nutrients to body. The objective of this study was to develop six formulations of granolas/cereal bars using different combination of Sunnah fruits such as dates (Phoenix dactylifera), raisins (Vitis vinifera L.) and figs (Ficus carica). The cereal bars were formulated using dry raw materials (glutinous rice, black Cummins, etc.) and binding agents (honey and glucose syrup). The cereal bars were assessed for water activity and proximate composition. It was observed that the sample B, made with 70 g of glucose syrup, 100 g honey and 450 g of total fruits had the highest value of moisture (18.73%) as compared to other formulations (P<0.05). There were no differences in protein contents of the cereal bars formulated. Ash contents of the formulations were significantly different (P<0.05) in samples B and F; the values ranged between 0.97% and 1.88%. The fat contents were significantly different with formulation B having the highest fat content (10.72%) and carbohydrate contents were affected by fibre contents; samples with lower crude fibres had higher carbohydrate contents which also reflect in the energy contents of the granola/cereal bar samples. Lowest a(w) (water activity) was observed in the samples with lower fruit contents which could be as a result of their lower moisture contents. According to the results, incorporation of glutinous rice flakes with different composition Sunnah foods and binding agents; honey and glucose syrup can be used to formulate cereal bars with appreciable proximate and energy contents. (c) All Rights Reserved